2022
DOI: 10.1002/aenm.202203190
|View full text |Cite
|
Sign up to set email alerts
|

Plant‐Derived l‐Theanine for Ultraviolet/Ozone Resistant Perovskite Photovoltaics

Abstract: carbon emission energy is an urgent issue for all countries in the century. Solar energy is the cleanest, safest, and most reliable energy in cognition. Perovskite photovoltaic technology has become a rising candidate in the photovoltaic field with its rapidly improved efficiency, simple preparation process, and low cost.Perovskite-based photovoltaic devices with great operation performance are inseparable from perovskite absorber materials with excellent performance, including a wide tolerance factor and adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 58 publications
2
33
0
Order By: Relevance
“…It is further confirmed that CNA is more conducive to reducing nonradiative recombination, which also contributes to increase open circuit voltage ( V OC ). [ 46 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is further confirmed that CNA is more conducive to reducing nonradiative recombination, which also contributes to increase open circuit voltage ( V OC ). [ 46 ]…”
Section: Resultsmentioning
confidence: 99%
“…It is further confirmed that CNA is more conducive to reducing nonradiative recombination, which also contributes to increase open circuit voltage (V OC ). [46] The matching arrangement of energy levels at the perovskite/HTL interface is crucial for photogenerated carrier transport and eventually collection by the electrode. On account of the relative arrangement of energy levels, the charge transport process at the perovskite/HTL interface is further analyzed on the basis of the Schottky-Mott limit.…”
Section: Resultsmentioning
confidence: 99%
“…68,69 Other distinctive functions are presented in the promotion of uniform and compact perovskite films by modulating the crystallization process such as nucleation and growth, and bandgap alignment through self-doping effect. 70,71 In most cases, the hydrophobic nature of the molecules also improves the ambient stability of the devices. GABr and GASCN are typically used as additives.…”
Section: Additive Engineeringmentioning
confidence: 99%
“…Semiconducting perovskites share a general chemical component of APbX 3 (A = Cs, FA, MA, or mixed‐halide; X = Cl, Br, I, or mixed‐halide) and crystal structure with corner‐shared [PbX 6 ] 4− octahedra. [ 13,14 ] There are weak van der Waals forces and loose ionic bonding within the perovskite crystal structure, which leads to abnormal distortion of the perovskite lattice and even component separation under operating conditions such as humidity, heat, and illumination exposure, [ 15–17 ] resulting in a large number of defects around the grain boundaries and top and bottom surfaces of the perovskite film, such as Pb, I vacancies and Pb─I antisites. [ 10,18,19 ] These unfavorable trap states, further acting as recombination centers, lead to severe nonradiative recombination, photogenerated carrier annihilation, and intrinsic degradation of perovskite materials.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first report of organic-inorganic hybrid lead halide perovskite solar cells (PSCs) by Miyasaka et al in 2009, [1] it has exposure, [15][16][17] resulting in a large number of defects around the grain boundaries and top and bottom surfaces of the perovskite film, such as Pb, I vacancies and Pb─I antisites. [10,18,19] These unfavorable trap states, further acting as recombination centers, lead to severe nonradiative recombination, photogenerated carrier annihilation, and intrinsic degradation of perovskite materials.…”
Section: Introductionmentioning
confidence: 99%